2002
DOI: 10.1002/rsa.10017
|View full text |Cite
|
Sign up to set email alerts
|

Extremal problems on set systems

Abstract: For a family F k = k 1 k 2 k t of k-uniform hypergraphs let ex n F k denote the maximum number of k-tuples which a k-uniform hypergraph on n vertices may have, while not containing any member of F k . Let r k n denote the maximum cardinality of a set of integers Z ⊂ n , where Z contains no arithmetic progression of length k. For any k ≥ 3 we introduce families F k = k 1 k 2 and prove thatholds. We conjecture that ex n F k = o n k−1 holds. If true, this would imply a celebrated result of Szemerédi stating that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
339
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 129 publications
(345 citation statements)
references
References 11 publications
5
339
0
1
Order By: Relevance
“…In this section we describe the regularity lemma for 3-uniform hypergraphs, due to Frankl and Rödl [6]. In the original Regularity Lemma of Szemerédi for graphs, it was shown that the vertex set of any large enough graph G can be partitioned into a bounded number of classes, such that the following holds: For almost every pair of vertex classes V i and V j , the bipartite subgraph of G induced by V i and V j is "very uniform," that is, its edges are distributed in much the same way as one would expect in a random bipartite graph.…”
Section: The Regularity Lemma For Hypergraphsmentioning
confidence: 99%
See 4 more Smart Citations
“…In this section we describe the regularity lemma for 3-uniform hypergraphs, due to Frankl and Rödl [6]. In the original Regularity Lemma of Szemerédi for graphs, it was shown that the vertex set of any large enough graph G can be partitioned into a bounded number of classes, such that the following holds: For almost every pair of vertex classes V i and V j , the bipartite subgraph of G induced by V i and V j is "very uniform," that is, its edges are distributed in much the same way as one would expect in a random bipartite graph.…”
Section: The Regularity Lemma For Hypergraphsmentioning
confidence: 99%
“…If the regularity condition fails to be satisfied for any ␣, we say that Ᏼ is (␦, r)-irregular with respect to G. This implies in particular that if Ᏼ is a dense hypergraph, then most of the triples of Ᏼ belong to (␦, r)-regular triads of the partition ᏼ. We now state the Regularity Lemma of [6]. …”
Section: Definition 26 We Refer To Any K-partite 3-uniform Hypergrmentioning
confidence: 99%
See 3 more Smart Citations